Implementasi Good Corporate Governance (GCG) Di Lembaga Perbankan Syariah - Permatasari, Karina Indah; Permatasari, Nabila Anugrah Putri; Djasuli, Mohamad (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
This paper examines the concept and implementation of Good Corporate Governance (GCG) in a banking company. GCG is a financial system with the aim of creating an economic system that benefits all parties involved. GCG implementation encourages the creation of healthy competition and a conducive business climate. Especially when GCG is implemented in the world of sharia banking, it will increasingly show the pioneering concept of Islam in realizing a sharia-based economic system. Performance appraisal of Islamic banks is very important for every bank stakeholder, namely bank management, customers, business partners and the government in a competitive financial market. The increase in the value of shares and the amount of third party funds is an indicator of increasing public trust in the bank concerned. GCG implementation is also relevant and in line with Islamic values. Good Corporate Governance (GCG) is an important principle in the activities and life of a Muslim. Islam very intensely teaches the application of the principles of 'ada (justice), tawazun (balance), akhlaq (moral), shiddiq (honesty), amanah (fulfillment of trust), fathanah (intelligence), tabligh (transparency).